Strategi Mobile Journalism dalam Meningkatkan Kinerja Peliputan Wartawan (Studi pada Media TribunBengkulu.com) - Wahyuningtias, Diah; Yuliati; Muzni, Nurlianti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Mobile Journalism (MOJO) has become a significant innovation in the field of journalism. MOJO has numerous effects on the performance of journalists in news coverage. This research investigates the use of MOJO as an effectibve tool to enchance responsiveness, engagement, and flexibility in carrying out journalistic tasks. Through a qualitative approach and case studies, this study explores the experiences of Tribun Bengkulu journalists who have adopted mobile journalism in converiing news in various locations. The research results indicat that the use of MOJO devices enables journalists to respond to news quickly and efficiently. With the ability to record videos, take photos, and engage in live broadcasts, journalists can cover events more dynamically. Futhermore, audience engagement is also enchanced through social media, particularly through live broadcasts. Financial affordability has proven to be an advantage, allowing media organizations with limited budgets to produce quality content without the need for expensive equipment. However, challenges related to production quality and ethical considerations need to remain a special focus. This can be addressed through specialized training and robust ethical guidelines for journalists adopting mobile journalism to ensure that high journalistic standards are maintained. In conclusion, MOJO is not just a practical tool for efficient news coverage but also an innovative approach that can enhance the engagement and flexibility of journalists in delivering information to the public.